Phytochemical Analysis, Antioxidant And Antimicrobial Activities Of Leaves Extract Of Date Palm Grown In Algeria - Laouini, S. E.; Segni, L.; Ouahrani, M. R.; Gherraf, N.; Mokni, S. (University of Eloued جامعة الوادي, 2012)
In this study, we have determined the phenolic compounds, antioxidant and antimicrobial activity of methanolic extracts from three varieties of leaves tree. According to the results the leaves extracts have very important values for polyphenols (215.24 to 156.46 mg GAE / g DW) and high antioxidant activity (324. 45 to 206.21 mg GAE / g DW), DPPH (IC50 = 2.98 to 4.83 μg / ml) and β-bleaching test (IC50 = 133. 93 to 194. 12 μg / ml); also the three extracts reveal a considerable antimicrobial potency and antifungal considerable activity , the diameter of inhibition is 14.4 ± 0.6 mm for Hamraya, 19.8 ± 0.5 mm for Ghars and 17.4 ± 0.8 mm for Deglet Nour (concentration 50 mg / ml) from Staphylococcus aureus ATCC.
Articale in Journal of fundamental and Applied Sciences Vol. 04 N. 02
Keywords: Phoenyx dactylifera; leaves extract; polyphenol; antioxidant; reducing power.